2011
DOI: 10.1186/1479-5868-8-78
|View full text |Cite
|
Sign up to set email alerts
|

How many steps/day are enough? for children and adolescents

Abstract: Worldwide, public health physical activity guidelines include special emphasis on populations of children (typically 6-11 years) and adolescents (typically 12-19 years). Existing guidelines are commonly expressed in terms of frequency, time, and intensity of behaviour. However, the simple step output from both accelerometers and pedometers is gaining increased credibility in research and practice as a reasonable approximation of daily ambulatory physical activity volume. Therefore, the purpose of this article … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
375
6
40

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 415 publications
(455 citation statements)
references
References 53 publications
24
375
6
40
Order By: Relevance
“…Total step counts are an index of MVPA in adults 7) and in children 8) , and have been monitored since 1989.…”
Section: Results Of the National Health And Nutrition Survey Of Japanmentioning
confidence: 99%
“…Total step counts are an index of MVPA in adults 7) and in children 8) , and have been monitored since 1989.…”
Section: Results Of the National Health And Nutrition Survey Of Japanmentioning
confidence: 99%
“…Regarding walking, instead of a goal of 10,000 steps/day as is recommended for healthy adults, different goals such as a range of 7000e10,000 steps/day for healthy older adults and a range of 6500e8500 steps/day for individuals with chronic illness or disability could be recommended. 50 Pedometers can also be used to motivate walking. 22,23 Group walking can be considered because participants can minimize safety concerns (e.g., falling) with peer support.…”
Section: Discussionmentioning
confidence: 99%
“…Results of an analysis by Tudor-Locke et al [40] showed that 60 minutes of moderate -to vigorousintensity PA (MVPA) in children appears to be achieved, on average, within a total volume of 13000 to 15000 steps per day in boys and 11000 to 12000 steps per day in girls. For adolescents (both boys and girls), 10000 to 11700 steps may be associated with 60 minutes of MVPA.…”
Section: Introductionmentioning
confidence: 99%